Familial Near-Total Intestinal Aganglionosis - Saida Hidouri; Hayet Zitouni; Jamila Chahed; Sana Mosbahi; Samia Belhassen; Amine Ksiaa; Badii Hmida; Imed Krichene; Lassad Sahnoun; Mongi Mekki; Mohsen Belguith; Abdellatif Nouri (EL-Med-Pub, 2017)
Near total aganglionosis represents the most extreme and rare form of Hirschsprung's disease. It can affect more than one member of family. We report three cases of near total intestinal aganglionosis in a family presenting with intestinal obstruction at birth. All of them were operated and a jejunostomy was performed. Outcome was dismal.